Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Untuk Meningkatkan Hasil Belajar Siswa Tentang Keberagaman Suku Dan Budaya Di Indonesia Siswa SD Kelas IV - Abdul Hakim; Yulia Yulia; Rahmadani Rahmadani (Universitas Negeri Makassar, 2022)
This research was motivated by the learning outcomes of fourth grade students of UPT SD Negeri 9 Benteng, Sidrap Regency who had not yet reached the predetermined minimum learning completeness standard (SKBM). The research approach used is a qualitative approach and the type of research used is classroom action research . Based on the data obtained, the research results in the first cycle showed the learning process was in sufficient qualification (C) and the learning test results were in sufficient qualification (C) while in the second cycle the research results on the learning process increased to good qualification (B) and the learning test results are in good qualification (B). Based on the results of the study, it can be concluded that the application of the two stay two stray type of cooperative learning model can improve the learning process and student learning outcomes about ethnic and cultural diversity in Indonesia in the fourth grade of UPT SD Negeri 9 Benteng, Sidrap Regency.